PERAN PEMERINTAH KOTA TANJUNGPINANG DALAM PENINGKATAN DAN PENGOPTIMALAN RETRIBUSI PARKIR DI KOTA TANJUNGPINANG - Hanthyta Dwi Karniya; Rudy Subiyakto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
The study aims to find out the extent of the tanjungpinang city government's role in the increasing and optimizing retribution placed in the city of Tanjungpinang. (PAD) the problem is that there is a growing instability of retribution for the original income area (PAD). Based on the interviews, researchers found that a weak level of surveillance conducted by the service in monitoring the performance of the parking attendants had a detrimental effect on the weakened valet initiative of giving parking tickets. So the process of accepting retribution of the parking for the pad does not reach the target ralisation. The research is packed with a descriptive qualitative approach to gain a deep understanding of the implementation of retribution parking in the Tanjungpinang city. The results of this study will eventually provide a solution to the problem of research. That the efforts of the Tanjungpinang in the increase and optimizing of the receipt of parking retribution are seen from regulatory indicators, facilitators, dynamitators, and moderators need to be maximized. Therefore, the Suggestions from this study to give greater attention to the level of sensitivity and monitoring of occurring phenomena by recommendations in the study. Thus, further research may shed light on the implementation of the implementation of the implementation of the bygone city government.